Adolescent Civic Involvement and the Great Recession of 2008: Testing the Certainty of Employment - Eric Suddeath; Laura Martin; Deidra Faye Jackson; Phillis George (The University of Alabama, 2022)
This study employs data from the Educational Longitudinal Study of 2002 to investigate the relationship between the voluntary civic involvement of high school students and their subsequent employment status during the Great Recession of 2008. It also examines whether volunteering with a specific type of community organization relates to future employment. Such youth civic involvement offers experiential learning in which students use academic knowledge and skills to address specific community needs. Along the pathways to employment, students achieve learning objectives while experiencing real-world issues. Using SPSS, the authors conduct a logistical regression, and discuss the results using odds ratios. The authors also include gender, ethnicity, family composition, parents' highest level of education, and family income as demographic variables.